The Effectiveness of Wound Book Diabetic Ulcer and Dressing on the Improvement of Modern Wound Care Knowledge in Professional Nurse Students of Universitas Muhammadiyah Purwokerto - Dea Alpariani; Meida Laely Ramdani (UM Purwokerto Press, 2021)
Wound care has developed very rapidly, especially in the last two decades which has been supported by advance health technology. In addition, the current issue of wound care management is related to changes in patient profiles which are increasingly accompanied by degenerative disease conditions and metabolic disorders. These conditions usually require proper treatment so that the healing process can be optimal, such as diabetes mellitus wounds. Based on these problems, innovation is needed that can help students learn about modern wound dressing in a book entitled wound book. It is an innovation in the form of a book to learn about proper and correct diabetic wound management and therapies that can accelerate the healing process of diabetic wounds with modern dressings. This study aimed to analyze the effectiveness of diabetic ulcers and dressings on the improvement of modern wound care knowledge in nurse students at Universitas Muhammadiyah Purwokerto. This was quantitative research that employed a one-group pretest-posttest design. The test was carried out to determine the improvement of knowledge before and after the study. The data were analyzed using the paired-sample t- test formula, in which it involved 30 nurse student. The result of the expert test showed that both media and material were in a very appropriate category. Moreover, the average scores were 4,64 and 4.60, respectively. The result above indicated that the average value of respondents' knowledge before and after being given a wound book media was 65.00 12.03 and 88.17 7,007, respectively. Meanwhile, the results of bivariate analysis using the paired-sample t-test revealed that the significance value was 0.000 (p-value 0.005).